The Role of Alternative Polyadenylation in the Regulation of Subcellular RNA Localization - Arora, Ankita; Goering, Raeann; Lo, Hei Yong G.; Lo, Joelle; Moffatt, Charlie; Taliaferro, J. Matthew (Frontiers in Genetics, 2022)
Alternative polyadenylation (APA) is a widespread and conserved regulatory mechanism that generates diverse 3' ends on mRNA. APA patterns are often tissue specific and play an important role in cellular processes such as cell proliferation, differentiation, and response to stress. Many APA sites are found in 3' UTRs, generating mRNA isoforms with different 3' UTR contents. These alternate 3' UTR isoforms can change how the transcript is regulated, affecting its stability and translation. Since the subcellular localization of a transcript is often regulated by 3' UTR sequences, this implies that APA can also change transcript location. However, this connection between APA and RNA localization has only recently been explored. In this review, we discuss the role of APA in mRNA localization across distinct subcellular compartments. We also discuss current challenges and future advancements that will aid our understanding of how APA affects RNA localization and molecular mechanisms that drive these processes.